Fence diagram drawn through test wells at the aquifer test site, showing zones of finer grained material of relatively low permeability interbedded with coarser grained sand and gravel, Piketon area south-central Ohio [carta] - Fidler, Richard E.; Norris, Stanley E. (Washington, DC : Department of the Interior, 1969)
PSZJBL